peranan MIKRONUTRIEN DENGAN KECENDERUNGAN TERPAPAR COVID-19 PADA ORANG DEWASA DI MEDAN ESTATE DELI SERDANG : Peranan Mikronutrien dengan Kecenderungan Terpapar COVID-19 pada Orang Dewasa di Medan Estate Deli Serdang - Novriani tarigan; Ginta Siahaan; Erlina Nasution (Universitas Airlangga, 2022)
Background: COVID-19 caused by SARS-Cov2 was reported by WHO that have infected people around the world and caused death. Indonesia was the country with the highest mortality compared to countries in Asia at around 7.2%. COVID-19 caused the decrease in body's immunity so that an adequate intake of vitamins A, E, C as well as iron and zinc minerals was needed to prevent the easy transmission of the COVID-19 virus. Objective: Assesing the role of micronutrients with the exposure tendency to COVID 19 in adults in Medan Estate, Deli Serdang. Methods: The research was observational with a cross sectional design. The population aged 30-58 years amounted to 158 people, while the sample was determined based on simple random sampling method and obtained sample of 61 people. Vitamins A, C, E intake as well as zinc and iron minerals were obtained using food recall for 3 days, then processed with Nutrisurvey. Meanwhile, the exposure tendency to COVID-19 was obtained by filling out a form about the symptoms experienced during the pandemic. Results: The results showed that the intake of vitamin A was in sufficient category of 58%, vitamin C was in less category of 69%, vitamin E was in less category of 61%, zinc was in less category of 54%, and iron in sufficient category of 53%. The results of statistical tests showed that there was correlation between intake of vitamins A, C and iron minerals to the exposure tendency to COVID 19, while vitamin E and zinc were not related to the exposure tendency to COVID 19. Conclusions: There was correlation between intake of vitamins A, C and iron minerals with a exposure tendency to COVID 19, while vitamin E and zinc were not associated with exposure tendency to COVID 19. Required adequate intake of nutrients in preventing transmission of Covid 19, also continues with obligation to comply health protocol that recommended by the Government.